2014
DOI: 10.1093/bja/aeu154
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids in the management of brain-dead potential organ donors: a systematic review

Abstract: Summary Current guidelines recommend the administration of hormonal combination therapy including immunosuppressive doses of corticosteroids to donors with low left ventricular ejection fractions and to consider hormonal therapy administration to all donors. However, these recommendations are largely based on observational data. The aim of this systematic review (SR) was to assess the clinical efficacy and safety of corticosteroids in brain-dead potential organ donors. MEDLINE and EMBASE were searched from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 51 publications
(35 reference statements)
0
35
0
5
Order By: Relevance
“…The rationale to add steroids in the donor is to block the upregulation of several pro‐inflammatory cytokines during the onset of brain death and improvement of hemodynamic instability following adrenal insufficiency . The evidence, however, is not robust based on a recent meta‐analysis . In addition, besides these potential benefits in DBD donors, their role in warm ischemic injury and DCD donation has never been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The rationale to add steroids in the donor is to block the upregulation of several pro‐inflammatory cytokines during the onset of brain death and improvement of hemodynamic instability following adrenal insufficiency . The evidence, however, is not robust based on a recent meta‐analysis . In addition, besides these potential benefits in DBD donors, their role in warm ischemic injury and DCD donation has never been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The observational studies generally show improved donor hemodynamics, oxygenation, organ procurement rates, graft survival, and recipient survival. 52 Brain-dead donor Table 2 Recommended combined hormone therapy for organ donors with an ejection fraction \ 40% or hemodynamic instability and consideration in all donors 37 Hormone Dose Anesthesia for organ donation surgery 533 treatment is typically cortisol (3-5 mgÁkg -1 qd) vs methylprednisolone (15-60 mgÁkg -1 or 3-5 g once or qd). 37,52 A retrospective review of brain-dead donor highdose (15 mgÁkg -1 methylprednisolone) vs low-dose (300 mg hydrocortisone) corticosteroid treatment found that low-dose treatment led to no difference in donor pulmonary or cardiac function, a similar organ transplantation rate, a decreased insulin requirement, and improved glycemic control.…”
Section: Pulmonarymentioning
confidence: 99%
“…Brièvement, ceux-ci mettent en jeu le relargage de cytokines pro-inflammatoires, l'expression tissulaire de protéines d'adhésion favorisant une infiltration tissulaire leucocytaire et des phénomènes d'apoptose cellulaire médiés notamment par la voie des caspases [23][24][25][26][27]. Cet état inflammatoire est susceptible d'entraîner des conséquences délétè-res pour les greffons et le receveur [28,29], conduisant certains à proposer un traitement anti-inflammatoire par corticoïdes, afin d'optimiser le prélèvement des greffons potentiels et leur qualité [30,31].…”
Section: Inflammation Systémique Et Phénomènes D'ischémie-reperfusionunclassified
“…Cet effet étant en dehors des objectifs de cette mise au point, nous ne détaillerons pas ici ces travaux, dont le niveau de preuve est faible et dont les résultats divergent. Cette stratégie pourrait néanmoins être intéressante pour le greffon pulmonaire [30,31]. D'un autre côté, une supplémentation en glucocorticoïdes à des doses plus faibles a été proposée afin de pallier l'insuffisance corticotrope induite par la ME, dans le but d'améliorer la défaillance hémodynamique du potentiel DDME [33,65].…”
Section: Vasopressineunclassified